Preparation method of core-shell structure carbon fiber / MoS2 photothermal conversion film and solar energy utilization device

Through the design of core-shell structure carbon/MoS2 porous fibers, the water transmission and shape preparation problems of the three-dimensional evaporator are solved, efficient water evaporation and complex shape manufacturing are achieved, and evaporation efficiency is improved.

CN120533984APending Publication Date: 2025-08-26GD POWER DEVELOPMENT CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510836464.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-21
Publication Date
2025-08-26

AI Technical Summary

Technical Problem

Existing three-dimensional solar evaporators face problems with water transmission channels and three-dimensional shape preparation process problems, resulting in evaporation efficiency being lower than the theoretical value.

Method used

Flexible carbon/MoS2 porous fibers with core-shell structure are used to manufacture three-dimensional evaporators through three-dimensional printing and mold pressing technology. Using the flexibility of carbon fiber and the photothermal conversion performance of MoS2 shell, combined with hollow fibers and surface porous structures, we can achieve rapid water transportation and evaporation balance.

Benefits of technology

The evaporation efficiency of the evaporator is improved to a maximum of 7.62 kg m-2 h-1, which is significantly more than 4.7 times that of traditional planar structures, and the device can be molded into various complex shapes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120533984A_ABST
    Figure CN120533984A_ABST
Patent Text Reader

Abstract

The invention discloses a core-shell structure carbon fiber / MoS2 photothermal conversion film preparation method and a solar energy utilization device. A preparation method of a core-shell structure carbon fiber / MoS2 photothermal conversion film comprises the following steps: S1, crushing bark fibers by adopting high-speed homogenization equipment to obtain porous nano carbon fibers; and S2, coating the surface of the porous nano carbon fiber with a MoS2 nanosheet by adopting a hydrothermal method to obtain the core-shell structure carbon / MoS2 fiber. The preparation method of the core-shell structure carbon fiber / MoS2 photothermal conversion film and the preparation method of the solar energy utilization device comprise the following steps: S3, printing a cylindrical mold by adopting a 3D printing technology; s4, injecting the core-shell structure carbon / MoS2 fiber dispersion liquid into a mold; s5, discharging the redundant water solution by adopting a die-casting method, and taking out the cylindrical device; and S6, after heating, a cylindrical device is obtained. The invention discloses a seawater evaporator for solar desalination. According to the invention, the prepared core-shell structure carbon fiber / MoS2 photothermal conversion film device has good hydrophilicity, salt elimination property and efficient evaporability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nanomaterial preparation, and in particular to a method and device for preparing a photothermal conversion film for desalinating seawater using solar energy. Background Art

[0002] Solar energy is considered an inexhaustible energy source, while water resources are becoming increasingly scarce. Solar evaporation technology, which converts sunlight into heat energy through photothermal materials, thereby evaporating water, is particularly important for alleviating pressing issues such as global water shortage and energy crises. However, current solar steam evaporators exhibit relatively low evaporation efficiencies, with traditional planar evaporators struggling to exceed 1.47 kg m -2 h -1 Currently, most efforts are focused on improving light absorption capacity and photothermal conversion efficiency by developing advanced photothermal materials. However, even if the light absorption rate exceeds 95% and the photothermal conversion efficiency reaches 98%, the evaporation efficiency cannot be substantially improved. Therefore, the evaporation rate of the current solar energy interface evaporator is often lower than the theoretical value of 1.47 kg m -2 h -1 .

[0003] To further improve the evaporation efficiency, researchers have developed three-dimensional (3D) solar evaporators, which have obvious advantages over traditional two-dimensional (2D) designs. By expanding the evaporation surface area through different geometric structures, the incident sunlight is captured and reflected, thereby improving the evaporation efficiency. However, most current three-dimensional structure designs face two prominent challenges. The first practical problem is the problem of water transmission channels caused by the difficulty of water absorption in three-dimensional structures. Although porous materials are recommended to promote water flow, this strategy is not enough to maintain evaporation balance, which in turn affects the long-term operation of the equipment. Another problem is that current photothermal conversion materials are difficult to meet the process requirements for designing three-dimensional evaporators of various shapes. Because most existing photothermal conversion materials cannot cope with the requirements of various preparation working conditions. Summary of the Invention

[0004] To address two challenges facing 3D evaporators—water transport and 3D shape fabrication—this invention provides a method for preparing flexible and shape-controllable carbon / MoS2 porous fibers with a core-shell structure. These fibers possess a hollow core and a porous surface, enabling rapid water transport. Furthermore, the fibers' flexibility allows for fabrication of devices of arbitrary shapes. A variety of 3D evaporators can be manufactured using 3D printing and mold pressing techniques.

[0005] The improved evaporation performance of the 3D evaporator can be attributed to the excellent light-to-heat conversion efficiency of the nano-MoS2 shell coating the carbon fiber surface, the interconnected porous structure of the hollow fibers and the surface, which facilitates rapid water transport and salt removal, and the good formability of the carbon / MoS2 fibers. The ultrafast water diffusion and hydrophilic properties of the interconnected porous film ensure a balance between evaporation and water supply during the steam process, which is crucial in the design of 3D evaporators.

[0006] To achieve the above objectives, the present invention provides a method for preparing a core-shell carbon fiber / MoS2 photothermal conversion film and a solar energy utilization device, comprising: S1. Using high-speed homogenization equipment to crush bark fibers to obtain porous nanocarbon fibers; S2, using a hydrothermal method to coat nano-MoS2 nanosheets on the surface of porous nano-carbon fibers to obtain core-shell structured carbon / MoS2 fibers; S3, using 3D printing technology to print a cylindrical mold; S4, injecting the core-shell carbon / MoS2 fiber dispersion into the mold; S5. Exhaust the excess aqueous solution by die-casting and remove the cylindrical device; S6. After heating, a cylindrical device is obtained.

[0007] Preferably, the hydrothermal reaction temperature of S2 is 150-200 °C, and the reaction time is 10-12 hours.

[0008] Preferably, in step S4, a cylindrical mold is printed using 3D printing technology; the mold shape can be: a pentagon, a hexagon, a cylinder, a rose, etc.

[0009] Compared with the existing technology, the present invention has the following advantages: the synthesized core-shell structure light-to-heat conversion film has high light-to-heat conversion performance, fast water transport performance and formability. The evaporation efficiency of the printed device can reach up to 7.62 kg m -2 h -1 , which provides 4.7 times that of the planar structure evaporator. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 The cylindrical device printed in Example 1 of the method for preparing the core-shell carbon fiber / MoS2 light-to-heat conversion film and the solar energy utilization device according to the present invention; Figure 2 This is an SEM image of the carbon / MoS2 fiber prepared in Example 1 of the method for preparing a core-shell carbon fiber / MoS2 light-to-heat conversion film and a solar energy utilization device according to the present invention; Figure 3This is an SEM image of the porous structure of the carbon / MoS2 fiber surface prepared in Example 1 of the method for preparing a core-shell carbon fiber / MoS2 light-to-heat conversion film and a solar energy utilization device according to the present invention; Figure 4 This is an SEM image of the porous structure of the carbon / MoS2 fiber cross section in Example 1 of the method for preparing a core-shell carbon fiber / MoS2 light-to-heat conversion film and a solar energy utilization device according to the present invention; Figure 5 This is an infrared imaging image of the cross section of the cylindrical device printed in Example 1 of the method for preparing the core-shell carbon fiber / MoS2 light-to-heat conversion film and the solar energy utilization device according to the present invention; Figure 6 Schematic diagram of a cylindrical structure evaporator assembled according to Example 1 of the method for preparing a core-shell structure carbon fiber / MoS2 light-to-heat conversion film and a solar energy utilization device of the present invention; Figure 7 Print out a rose-shaped evaporator schematic diagram according to Example 2 of the method for preparing a core-shell carbon fiber / MoS2 photothermal conversion film and a solar energy utilization device of the present invention; Figure 8 Print out an infrared image of the rose-shaped evaporator surface according to the method for preparing the core-shell structure carbon fiber / MoS2 photothermal conversion film and the solar energy utilization device embodiment 2 of the present invention; Figure 9 Print out a five-pointed star shaped evaporator according to the method for preparing the core-shell structure carbon fiber / MoS2 photothermal conversion film and the solar energy utilization device embodiment 4 of the present invention; Figure 10 The hydrophilicity test of a semicircular evaporator is printed out according to the method for preparing a core-shell carbon fiber / MoS2 photothermal conversion film and a solar energy utilization device according to Example 5 of the present invention; DETAILED DESCRIPTION

[0011] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention. Example 1

[0012] S1. Pulverize bark fibers using a high-speed homogenizer to obtain porous carbon nanofibers: Weigh 10 g of bark fibers and immerse them in 500 mL of a 0.1 wt.% KOH solution. Use a homogenizer at 600 rpm to process the suspension, ultrasonicate for 10 minutes, and repeat this process eight times. Finally, filter the suspension and dry it to obtain porous carbon nanofibers.

[0013] S2. Using a hydrothermal method, MoS2 nanosheets were coated on the surface of porous nanocarbon fibers to obtain core-shell carbon / MoS2 fibers. Dissolve 2.5 g of ammonium molybdate and 5 g of thiourea in 500 mL of deionized water and stir. Dissolve 1 g of nanocarbon fibers in 60 mL of this solution and sonicate for 10 minutes. The mixture was then transferred to a 100 mL reaction vessel and reacted at 200°C for 12 hours. After cooling, the resulting fibers were washed with distilled water and dried at 80°C for 12 hours to obtain carbon / MoS2 fibers.

[0014] S3. Use 3D printing technology to print a cylindrical mold: cylindrical diameter 15 mm, cylindrical wall thickness 3 mm, cylindrical height 30 mm.

[0015] S4. Injecting the core-shell carbon / MoS2 fiber dispersion into the mold: the mass concentration of the dispersion is: 20%.

[0016] S5. Use the die-casting method to drain the excess aqueous solution and take out the cylindrical device: the die-casting pressure is 20 kPa.

[0017] S6. After heating, a cylindrical device is obtained. The specific preparation process is shown in the attached Figure 1 .

[0018] The SEM images of the synthesized porous carbon / MoS2 fibers are attached. Figure 2 The surface of the hollow fiber is coated with a layer of MoS2 nanosheets. The surface porous structure of the prepared porous carbon / MoS2 fiber membrane is shown in the attached Figure 3 , the internal cross porous structure is attached Figure 4 The printed cylindrical device is attached. Figure 1 The temperature distribution diagram of the side of this cylindrical structure under the sun is shown in the attached figure. Figure 5 The schematic diagram of this cylindrical evaporator is shown in the attached Figure 6 As shown, under one sun intensity, the evaporation rate is 7.62 kgm −2 h −1 . Example 2

[0019] Steps S1 to S3 are the same as steps S1 to S3 in Example 1.

[0020] S4. Injecting the core-shell carbon / MoS2 fiber dispersion into the mold: the mass concentration of the dispersion is 5%.

[0021] S5. Use the die-casting method to drain the excess aqueous solution and remove the rose-shaped device: the die-casting pressure is 10 kPa.

[0022] S6. After heating, a rose-shaped device is obtained.

[0023] The printed rose-shaped device is attached. Figure 7 The surface temperature diagram of this cylindrical structure under one sun is shown in the attached figure. Figure 8 As shown. Under the intensity of one sun, the evaporation rate of this rose-shaped device is 8.91 kgm −2 h −1 . Example 3

[0024] Steps S1 to S6 are the same as steps S1 to S6 in Example 1.

[0025] S3. Use 3D printing technology to print a cylindrical mold: cylindrical diameter 3 mm, cylindrical wall thickness 2 mm, cylindrical height 20 mm.

[0026] The evaporation rate of this evaporator under one sun is 4.57 kgm −2 h −1 . Example 4

[0027] S1. Pulverize bark fibers using a high-speed homogenizer to obtain porous carbon nanofibers: Weigh 10 g of bark fibers and immerse them in 500 mL of a 0.1 wt.% KOH solution. Use a homogenizer at 600 rpm to process the suspension, ultrasonicate for 10 minutes, and repeat this process eight times. Finally, filter the suspension and dry it to obtain porous carbon nanofibers.

[0028] S2. Using a hydrothermal method, MoS2 nanosheets were coated on the surface of porous nanocarbon fibers to obtain core-shell carbon / MoS2 fibers. Dissolve 2.5 g of ammonium molybdate and 3.8 g of thiourea in 500 mL of deionized water and stir. Dissolve 1 g of nanocarbon fibers in 60 mL of this solution and sonicate for 10 minutes. The mixture was then transferred to a 100 mL reaction vessel and reacted at 150°C for 10 hours. After cooling, the mixture was washed with distilled water and dried at 80°C for 12 hours to obtain carbon / MoS2 fibers.

[0029] S3. Use 3D printing technology to print a five-pointed star-shaped mold: the five-pointed star shape has an outer diameter of 15 mm, an inner diameter of 10 mm, and a thickness of 10 mm.

[0030] S4. Injecting the core-shell carbon / MoS2 fiber dispersion into the mold: the mass concentration of the dispersion is 30%.

[0031] S5. Use the die-casting method to drain the excess aqueous solution and take out the cylindrical device: the die-casting pressure is 50 kPa.

[0032] S6. After heating, a five-pointed star-shaped device is obtained.

[0033] The printed five-pointed star shaped device is attached. Figure 9 The evaporation rate of this five-pointed star-shaped device under one sun is 2.72 kgm −2 h −1 . Example 5

[0034] S1. Pulverize bark fibers using a high-speed homogenizer to obtain porous carbon nanofibers: Weigh 10 g of bark fibers and immerse them in 500 mL of a 0.1 wt.% KOH solution. Use a homogenizer at 600 rpm to process the suspension, ultrasonicate for 10 minutes, and repeat this process eight times. Finally, filter the suspension and dry it to obtain porous carbon nanofibers.

[0035] S2. Using a hydrothermal method, MoS2 nanosheets were coated on the surface of porous nanocarbon fibers to obtain core-shell carbon / MoS2 fibers. Dissolve 2.5 g of ammonium molybdate and 6.2 g of thiourea in 500 mL of deionized water and stir. Dissolve 1 g of nanocarbon fibers in 60 mL of this solution and sonicate for 10 minutes. The mixture was then transferred to a 100 mL reaction vessel and reacted at 180°C for 12 hours. After cooling, the mixture was washed with distilled water and dried at 80°C for 12 hours to obtain carbon / MoS2 fibers.

[0036] S3. Use 3D printing technology to print a semicircular mold: the semicircular outer diameter is 15 mm and the height is 10 mm.

[0037] S4. Injecting the core-shell carbon / MoS2 fiber dispersion into the mold: the mass concentration of the dispersion is 15%.

[0038] S5. Use the die-casting method to drain the excess aqueous solution and take out the cylindrical device: the die-casting pressure is 20 kPa.

[0039] S6. After heating, a semicircular device is obtained.

[0040] The printed semicircular device is super hydrophilic, see attached Figure 10 In 0.25 s, the water droplet completely penetrates into the fiber membrane. The evaporation rate of this five-pointed star-shaped device under one sun is 2.25 kgm −2 h −1 .

[0041] The number of devices and processing scales described herein are intended to simplify the description of the present invention, and applications, modifications, and variations of the present invention will be apparent to those skilled in the art.

[0042] Although the embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the description and implementation methods. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and illustrations shown and described herein.

Claims

1. A method for preparing a core-shell carbon fiber / MoS2 photothermal conversion film and a solar energy utilization device, characterized in that: The following steps are involved: S1. Using high-speed homogenization equipment to crush bark fibers to obtain porous nanocarbon fibers; S2. Using a hydrothermal method, nano-MoS2 nanosheets are coated on the surface of porous nano-carbon fibers to obtain core-shell carbon / MoS2 fibers; a method for preparing a core-shell carbon fiber / MoS2 photothermal conversion film and a method for preparing a solar energy utilization device; S3. Using 3D printing technology to print a cylindrical mold; S4. Injecting the core-shell carbon / MoS2 fiber dispersion into the mold; S5. Expelling the excess aqueous solution using a die-casting method and taking out the cylindrical device; S6. After heating, obtaining the cylindrical device.

2. The method for preparing the core-shell carbon fiber / MoS2 photothermal conversion film and the solar energy utilization device according to claim 1, characterized in that: In step 1, the bark fiber is crushed by a high-speed homogenization device, and the processing liquid is a 0.1 wt.% KOH solution.

3. The method for preparing the core-shell carbon fiber / MoS2 photothermal conversion film and the solar energy utilization device according to claim 1, characterized in that: In step S1, the bark fibers were crushed by a high-speed homogenization device at a speed of 600 rpm for 8 times, each time for 10 minutes.

4. The method for preparing the core-shell carbon fiber / MoS2 photothermal conversion film and the solar energy utilization device according to claim 1, characterized in that: Step S2: using a hydrothermal method to coat nano-MoS2 nanosheets on the surface of porous nano-carbon fibers to obtain a core-shell structure; the mass ratio of the initiator ammonium molybdate and thiourea is 1:1.5-2.

5.

5. As claimed in claim 4, the hydrothermal reaction temperature is 150-200°C, the reaction time is 10-12 hours, and after cooling, the product is washed with distilled water and dried at 80°C for 12 hours to obtain carbon / MoS2 fibers.

6. The method for preparing the core-shell carbon fiber / MoS2 photothermal conversion film and the solar energy utilization device according to claim 1, characterized in that: Step S3: Printing a cylindrical mold using 3D printing technology; The mold shape can be: pentagonal star, hexagonal, cylindrical, rose-shaped, etc.

7. The cylindrical structure as claimed in claim 6, wherein the cylindrical diameter or other shape diameter is 3-20 mm.

8. The cylindrical structure as claimed in claim 6, wherein the cylindrical wall thickness or the wall thickness of other shapes is 2-5 mm.

9. The cylindrical structure according to claim 6, wherein the height of the cylindrical structure is 10-50 mm.

10. The method for preparing the core-shell carbon fiber / MoS2 photothermal conversion film and the solar energy utilization device according to claim 1, characterized in that: S4. Injecting the core-shell carbon / MoS2 fiber dispersion into the mold; the mass concentration of the dispersion is: 5-30%.

11. The method for preparing the core-shell carbon fiber / MoS2 photothermal conversion film and the solar energy utilization device according to claim 1, characterized in that: Step S5: Use a die-casting method to discharge the excess aqueous solution and take out the cylindrical device; the die-casting pressure is 10-50 kPa.